Symposium 5: An Assessment of ICT-based Education for Mechanical Engineering in TEI Patras, Greece - Kabouridis, Georgios (Proceedings of the International Conference on Networked Learning, 2008)
Information and communication technologies (ICTs) can facilitate the education of mechanical engineers. The implementation of e-education leads staff to new roles and unknown activities. ICT-based education for mechanical engineering is a new learning approach that is seen to take place within communities of practice. In the new context of education there are new players in e-education, and the roles of the players have changed. The results on the educational process that have been accumulated during the last three years of using the e-learning material in Mechanical engineering department are presented. The educators and the students described several detailed examples related to some subject matter. The educators strongly believe (80%) that the best strategy for achieving the learning goals is the presence of the students in the class. Students agree with above approach only by 60% as the rest of them find very useful the availability of the didactic material in the internet.Only 50% of the students expressed their opinion about the quality of the courses to restricted accessibility to internet facilities from their homes. Above fact was expected as Kabouridis and Kakarelidis (2006) at their research amongst the students found that 72% own a personal computer at their home and 60% have ADSL internet access -a prerequisite condition to use e-learning effectively-.The agree that e-education does not provide the opportunity of learning by doing which is very essential for the future engineers. The majority of educators and students agree that e-learning material doesn’t cover the need of hands-on activities and it must be improved. The virtual experiments give the same results for the same inputs which is not the case for the real life problems. The active participation of the students is missing.The lecturers of TEI do not appreciate the ICT as a mean of personal connection with their students and their colleagues; they consider it as very cold. TEI of Patras did not embraced the new technology in the whole University -only four departments decided to participate in this pilot application of e-education-. As a consequence of this policy the learning environment has not been expanded in the whole community. (Wenger 1998). The educators strongly believe that ICT make the students "passive recipients of knowledge". Kenway and Bullen (2000) point out that ICT wide implementation will bring more fundamental changes in the way educational institutes operate and most probably it will influence the future of the society. The majority of the teachers at the beginning of the project accepted the commitment to produce didactic material for the e-education but in the following years 80% of them did not enriched it. The above results are in accordance with Laurillard (2002) who makes important points about the lack of conceptual frameworks and the variability of academics engagement with ICTs, which reduce the potential gains they might offer. The main reason for this attitude is based on the lack of staff training policy and support for the production of e-education materials. As a matter of fact students are not encouraged by the educators to use the facilities of the website.